Heterotrimeric G Proteins in Plants: Canonical and Atypical Gα Subunits - Natsumi Maruta (MDPI AG, 2021)
Heterotrimeric GTP-binding proteins (G proteins), consisting of Gα, Gβ and Gγ subunits, transduce signals from a diverse range of extracellular stimuli, resulting in the regulation of numerous cellular and physiological functions in Eukaryotes. According to the classic G protein paradigm established in animal models, the bound guanine nucleotide on a Gα subunit, either guanosine diphosphate (GDP) or guanosine triphosphate (GTP) determines the inactive or active mode, respectively. In plants, there are two types of Gα subunits: canonical Gα subunits structurally similar to their animal counterparts and unconventional extra-large Gα subunits (XLGs) containing a C-terminal domain homologous to the canonical Gα along with an extended N-terminal domain. Both Gα and XLG subunits interact with Gβγ dimers and regulator of G protein signalling (RGS) protein. Plant G proteins are implicated directly or indirectly in developmental processes, stress responses, and innate immunity. It is established that despite the substantial overall similarity between plant and animal Gα subunits, they convey signalling differently including the mechanism by which they are activated. This review emphasizes the unique characteristics of plant Gα subunits and speculates on their unique signalling mechanisms.